The simultaneous removal of NO and SO2 over MnO2 material via the multi-stage fluidized bed process at low temperatures. (15th February 2023) - Li, Changming; Zhang, Xiaoling; Li, Yunjia; Sun, Lixin; Huangfu, Lin; Li, Jianling; Gao, Shiqiu; Yu, Jian
Highlights: Multi-stage fluidized bed (MSFB) is explored for the purification of flue gas. MnO2 is used as the active medium in MSFB to simultaneously remove NO and SO2 . 100% removal efficiency of both NO and SO2 is achieved in the four-stage MSFB. The MSFB system can run stably in the presence of 10 vol% H2 O steam below 200 °C. The MnO2 is converted to MnSO4 which can be easily regenerated by ammonia water. Abstract: To overcome the easy poisoning and deactivation of denitrification catalysts by SO2 at low temperatures, the bench-scale multi-stage fluidized bed (MSFB) process with the active MnO2 medium (feeding rate of 0.3–1.2 kg/h) is designed and applied to simultaneously remove the NO and SO2 from flue gas of medium/small industrial boilers in the low-temperature range of 100 – 200 °C, which demonstrates excellent and stable removal efficiency of both NO and SO2 even in the presence of 10 vol% water. In the MSFB system, the fluidized MnO2 particles in different layers flow against the simulated flue gas stage by stage, and the deactivated MnO2 will be continuously discharged and replaced with fresh MnO2 to keep the system effective and steady. The MnO2 medium acts as both denitrification (DeNO x ) catalyst and desulfurizer, and the limited backmixing and layered arrangement of the MSFB system ensure the high removal capacity and sufficient utilization of MnO2 material. The multiple structural characterizations further reveal that the active MnO2 is gradually consumed by SO2 to form MnSO4 stage by stage with decreased specific surface and pore volume, accounting for its gradually decreased removal efficiency of both NO and SO2 stage by stage. And the deactivated MnO2 can be easily regenerated by aqueous ammonia with the conversion of MnSO4 to active MnO2 . The demonstrated advantages of the MSFB system with MnO2 will provide a promising technical route for the simultaneous removal of NO and SO2 from low-temperature flue gas in industry.